Wear-resistant granite ceramic tile with three-dimensional decorative effect and preparation method thereof
Through polycrystalline phase wear-resistant blank formulation and digital spraying technology, the shortcomings of granite in terms of stain resistance, weather resistance and strength are solved, and wear-resistant granite ceramic tiles with high hardness and wear resistance are achieved to meet high-end buildings and Decoration needs of public places.
Patent Information
- Application Number
- CN202411486784.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-23
AI Technical Summary
As a natural stone, granite has problems such as non-renewability, poor stain resistance, poor weather resistance, low strength and radioactive risks, and it is difficult to meet the needs of high-end building decoration and public places.
The polycrystalline phase wear-resistant blank formulation is used for high-temperature firing to generate a high-hard wear-resistant decorative layer. Combined with digital spraying technology and surface modifiers, wear-resistant granite ceramic tiles with three-dimensional decorative effect.
It achieves high hardness, wear resistance, stain resistance and strength of the product, and has the aesthetic effect of natural granite, meeting the market demand for higher hardness and wear resistance.
Smart Images

Figure CN119409485A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of granite ceramic tiles, and in particular relates to a wear-resistant granite ceramic tile with a three-dimensional decorative effect and a preparation method thereof. Background Art
[0002] Outdoor decoration has always preferred natural stone. Granite, as a natural stone, is mainly composed of minerals such as feldspar and quartz, with a Mohs hardness of 6 to 7. Because granite has a uniform structure, hard texture, wear resistance, and beautiful appearance, the products processed from it are well-proportioned, harmoniously concave and convex, and can show natural traces of history in the trend of grain and texture. Therefore, it is widely used in high-end architectural decoration projects such as villas, gardens, and communities, as well as public places with large traffic such as leisure squares, municipal projects, landscaping, subway train stations, etc.
[0003] However, as a natural stone directly taken from nature, granite is non-renewable, and with the increasing depletion of mineral resources and the country's efforts to improve the environment, the mining and use of granite are greatly restricted; in addition, granite has certain disadvantages when used for decoration, such as poor stain resistance, poor weather resistance, low strength, radioactive risks, and affecting the bearing capacity of buildings. Therefore, it is necessary to develop a new decorative material to replace natural granite, so that its surface effect is close to that of granite, and its physical and chemical properties reach or exceed those of natural granite. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant granite ceramic tile and its preparation method which uses a polycrystalline phase body formula to be fired at high temperature to react and generate a high-hardness wear-resistant decorative layer, so that the product has the properties of high hardness and good wear resistance of natural granite, as well as better physical and chemical properties such as pollution resistance, strength and radioactivity, and has a three-dimensional decorative effect.
[0005] The technical solution of the present invention is the wear-resistant granite ceramic tile with three-dimensional decorative effect, which is special in that the polycrystalline wear-resistant green body formula is composed of the following components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burnt talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, green body reinforcing agent 0 to 1%, and debonding agent 1 to 3%; the fine corundum powder is α-Al2O3 with an Al2O3 content of 99.9 to 100%, an Fe2O3 content of 0 to 0.1%, and the particle size D50 is less than 3μm.
[0006] Preferably, the chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O315-20wt%, SiO265-75wt%, K2O 2-5wt%, Fe2O30-4wt%, Na2O2-5wt%, CaO 0-2wt%, MgO0-1wt%, Li2O 0.3-1wt%, trace elements ≥0.1wt%, and loss on ignition 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm; the trace elements include rubidium, gallium, strontium, cadmium, and nickel; the ZrO2 content of the ultrafine zirconium silicate is greater than 64%, and the particle size D50 is less than 1μm.
[0007] Preferably, the high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96%, volatile matter at 105° ≤0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.
[0008] The technical solution of the present invention is a method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect, which is special in that it includes the following steps:
[0009] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain polycrystalline wear-resistant green body formula slurry, and after iron removal, send it to the transfer slurry pool for storage and aging for standby use;
[0010] (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, add different color pigments of set proportions to the polycrystalline wear-resistant blank formula slurry in step (1), stir evenly and send to the spray drying tower for powdering to obtain color powder and store it for aging for later use;
[0011] ⑶ Modification of color powder: adding a surface modifier to the stale qualified color powder in step ⑵, and modifying the performance of the color powder by a dry mixing process to obtain a modified color powder;
[0012] (4) Whole-body fabric: The prepared modified color powders of different colors are formed into a three-dimensional decorative blank layer according to a preset pattern through a CNC fabric system;
[0013] ⑸ Pressing and molding: Pressing the blank layer into a wear-resistant blank;
[0014] (6) Printing alignment code: Printing code on the wear-resistant blank of step (5) according to the corresponding pattern number;
[0015] ⑺Dry the formed green body and spray water on the surface of the dried green body to moisten the surface;
[0016] ⑻ Based on the multi-crystalline wear-resistant body formula in step ⑴, ceramic colorant, kaolin color slurry and raw materials are introduced, and color slurry is obtained through calcination, grinding and spray drying;
[0017] (9) Using the color slurry of step (8), according to the printing code of step (9), the wetted blank is sprayed with a digital spraying process in accordance with the same preset pattern as the blank to form a decorative wear-resistant layer;
[0018] ⑽ The bottom of the green body in step ⑼ is coated with base slurry;
[0019] ⑾ Send the green body coated with the base slurry into a roller kiln for high-temperature firing;
[0020] ⑿ Processing the fired products to obtain wear-resistant granite ceramic tiles with three-dimensional decorative effects.
[0021] As a preferred embodiment: the different color pigments in step (2) include ceramic pigments of different colors such as blue, red, yellow, black, green, etc.; the color powder is provided with 3 to 6 different colors according to the design requirements;
[0022] As a preferred embodiment: the spray drying tower in step (2) adopts a centrifugal spray drying system; the drying chamber diameter of the centrifugal drying system is greater than 5000mm, the drying output is 5-10t / h, the speed of the centrifugal atomizer is controlled to be 50-350r / s, and the particle gradation of the color powder is obtained: the particles under the 30 mesh sieve account for 100%, the particles between 40 mesh and 60 mesh account for 20%-25%, the particles between 60 mesh and 80 mesh account for 40%-45%, the particles between 80 mesh and 100 mesh account for 15%-20%, the particles below 100 mesh account for <3%, and the specific gravity of the color powder is 1.0-1.2g / cm 3 , the angle of repose is 30°~32°.
[0023] As a preference: in step (3), the modified color powder is composed of the following components by weight percentage: color powder: 97-99wt%, surface modifier: 1-3wt%; the surface modifier is one or a combination of the following: calcium stearate, aluminum stearate, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid-polyoxyethylene, aminopropyl triethoxysilane, trimethoxysilane, dimethoxysilane, polyphosphate, alkylbenzene sulfonate;
[0024] As a preferred embodiment: in step (5), the pressing pressure is > 40 MPa / cm 2 , brick thickness 9mm~40mm;
[0025] As a preference: the drying time in step (7) is 50 to 120 minutes; the residual moisture content of the green body after drying is ≤0.5%.
[0026] As a preferred embodiment: the CNC material distribution system in step (4) is an automatic operation technology directly controlled by digital information, which can simultaneously realize the distribution of 4 to 10 different color powders, and its structure includes four parts: a central control device, a material distribution device, a transfer storage mechanism and a transportation mechanism; the central control device is used for presetting, adjusting and outputting CNC patterns, and controlling the operation of the CNC material distribution system; the material distribution device arranges the blank layer according to the pattern texture preset in the central control device, and can be set up in several groups according to the thickness requirements of the blank layer, and the aperture of the material distribution nozzle is 1 to 5 mm; the transfer storage mechanism is used to store powders of different colors, and 4 to 10 groups are set up according to the distribution needs; the transportation mechanism is used to connect the transfer storage mechanism and the material distribution device to ensure that the color powder can be accurately and quickly transported to the material distribution device for blank layer arrangement; the three-dimensional decorative blank layer is formed by the CNC material distribution system using CNC technology according to the preset pattern, and the fabric texture is a consistent pattern texture formed from the bottom to the top of the blank layer, and the thickness of the material layer is 18 mm to 80 mm.
[0027] As a preferred embodiment: the color slurry in step (8) is composed of the following components by weight: 95-99% base slurry and 1-5% ceramic colorant; after being prepared by weight percentage, the color slurry is obtained by stirring evenly, and the specific gravity of the color slurry is 1.75±0.5g / cm 3 , 40° viscosity is 60-150mpa.s, D50 particle size is 10μm-15μm; the ceramic colorant is composed of one or more of blue, red, yellow, black and green; the base slurry is composed of the following components by weight percentage: light-fired wear-resistant material 78-90%, kaolin 8-20%, CMC 0.2-1%, trimer 0.5-1%, defoamer 0.2-1%; the formula composition of the light-fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank, the difference is that light-fired processing is required;
[0028] Preferably, the light-fired processing is as follows: after the formula is prepared according to the weight percentage, it is ball-milled into mud according to the wet process; the mud has a moisture content of 35-40%, a viscosity of 40°C of 40-80mpa.s, and a D50 particle size of 3-6μm; the ball-milled mud is spray-dried to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1050-1150°C to obtain a light-fired wear-resistant material.
[0029] Preferably, the decorative wear-resistant layer described in step (9) is formed by decorative printing using a plurality of different color slurries according to a preset pattern texture using a CNC spraying process. The digital spraying pattern is the same as the preset pattern texture of the blank CNC fabric. The pattern is narrowed by 0.2mm to 0.4mm, and the thickness of the decorative wear-resistant layer is 0mm to 1mm. The digital spraying process uses digital information to directly control the printing, and can simultaneously realize the printing of 4 to 10 different color slurries, and the printing amount per square is controlled to be 0 to 1800g.
[0030] Preferably, the high temperature firing described in step ⑾ adopts a kiln with a length of more than 300m, an inner width greater than 2m, a firing temperature of 1180-1250°C, a firing time of 60-120 minutes, a water absorption rate of the product after firing of ≤0.5%, and a Ra value of the product out of the kiln, where the Ra value refers to the arithmetic mean deviation of the profile, that is, the surface roughness is between 1.5 and 3μm.
[0031] As a preferred embodiment, the processing described in step ⑿ includes two situations:
[0032] ⑴ Grind the edges of the product after firing in step ⑾ directly;
[0033] (2) The product obtained in step (10) is first polished and then edged;
[0034] Among them, the polishing is the polishing of the wear-resistant surface; the polishing process parameters are: the polishing machine pressure is below 0.6Mpa, the polishing speed is 15-30m / min, the polishing abrasive blocks are matched as follows: 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, the polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] ⑴ In the polycrystalline wear-resistant green body formula of the present invention, by introducing fine corundum powder, lithium tailings, ultrafine zirconium silicate and titanium dioxide powder, and cooperating with the use of other raw materials, the green body reacts more fully during the sintering process, promoting the production of a variety of high-hardness wear-resistant crystals including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite, etc., and improving the strength and wear resistance of the ceramic.
[0037] (2) The digital spraying decoration method adopted in the present invention can use a variety of different colored slurries for spraying according to the preset pattern texture. The digital spraying pattern is the same as the pattern texture preset in the CNC cloth of the blank. The printing process is directly controlled by digital information, which greatly increases the convenience of production. It breaks through the disadvantage that traditional glaze spraying cannot be aligned, expands the richness of pattern design, and achieves the overall decorative effect of the product pattern texture from the inside to the outside. At the same time, the glaze slurry used for digital spraying is prepared by lightly firing the formulated raw materials and then wet-ball milling them to make wear-resistant glaze slurry. The light firing process promotes the growth of wear-resistant crystals, so that the product reaches or even exceeds the surface hardness and wear resistance of natural granite, and meets the market demand for granite ceramic tiles with higher hardness and wear resistance.
[0038] ⑶ In order to meet the precision requirements of digital powder spraying technology and decorative pattern effects, the present invention introduces surface modifiers such as calcium stearate and trimethoxysilane into the color powder of digital spraying. The hydrophilic group of the modifier can react physically and chemically with the surface of the inorganic powder and adsorb on the surface of the particle, so that the surface of the inorganic powder changes from hydrophilic to hydrophobic, thereby improving the surface activity of the inorganic powder material, improving the dispersion and flow properties of the powder, avoiding agglomeration or friction in the digital powder spraying process that causes blockage of the nozzle and the conveying pipeline, affecting the distribution effect and efficiency of the digital powder spraying, enriching the product detail display effect, and further broadening the terminal application space of wear-resistant granite ceramic tiles.
[0039] ⑷ The formula of the present invention introduces a large amount of fine corundum powder, which can increase the aluminum content of the formula and at the same time enhance the reaction activity of the green body during the sintering process, thereby promoting the formation of wear-resistant crystals such as mullite, feldspar, and corundum; the introduction of ultrafine zirconium silicate and titanium dioxide powder into the formula can promote the formation of zircon and rutile crystals, both of which are high-hardness materials and can better enhance the wear resistance of the product.
[0040] ⑸ The present invention grinds the lithium tailings into fine powder and introduces them into the green body formula. In addition to conventional elements such as silicon, aluminum, potassium, and sodium, the lithium tailings also contain special elements such as rubidium, gallium, strontium, cadmium, and nickel, and have a high SiO2 content. Fine grinding can promote the fluxing effect of trace elements, while enhancing the reaction activity of SiO2 and promoting the growth of quartz crystal phase. The introduction of lithium and the formation of quartz crystals can improve the wear resistance of granite ceramic tiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a diagram showing the physical phase detection results of a ceramic tile prepared by the method of Example 1 of the present invention;
[0042] Figure 2 This is a graph showing the phase detection results of the ceramic tile prepared by the method of Comparative Example 1;
[0043] Figure 3This is a graph showing the phase detection results of the ceramic tile prepared by the method of Comparative Example 2;
[0044] Figure 4 This is a rendering of the wear-resistant granite ceramic tile of the present invention. DETAILED DESCRIPTION
[0045] The present invention will be further described in detail below in conjunction with embodiments:
[0046] Embodiment 1:
[0047] A method for preparing wear-resistant granite ceramic tiles with three-dimensional decorative effects comprises the following steps:
[0048] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain the polycrystalline wear-resistant green body formula slurry, and send it to the transfer slurry pool for storage and aging after iron removal;
[0049] The polycrystalline wear-resistant blank formula is composed of the following components by weight percentage: 9.55% ball clay, 10% high white kaolin, 12% mixed mud, 4% burned talc, 4% bentonite, 19% potassium sodium stone powder, 10% finely ground lithium tailings, 5% calcined bauxite, 20% fine corundum powder, 3% ultrafine zirconium silicate, 2% high-purity anatase titanium dioxide powder, 0.35% blank reinforcing agent, and 1.1% debonding agent.
[0050] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.94% and a Fe2O3 content of 0.06%; the particle size D50 is 1.86 μm;
[0051] The chemical composition of the finely ground lithium tailings is as follows by weight percentage: Al2O3 17.83wt%, SiO2 69.11wt%, K2O 3.50wt%, Fe2O3 0.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li2O 0.41wt%, trace elements 0.18wt%, and ignition loss 3.39wt%. The trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel; the particle size D50 is 5.4μm;
[0052] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0053] The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of 98.6%, a powder whiteness value of 97.2%, a volatile matter of 0.3% at 105°, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;
[0054] ⑵ Preparation of powders of different colors: according to the requirements of texture pattern design, a certain proportion of different color pigments are added to the polycrystalline wear-resistant blank formula slurry in step ⑴, stirred evenly and sent to a spray drying tower for powdering to obtain color powder and store it for aging for later use;
[0055] The color powder is provided in four types, specifically including:
[0056] The polycrystalline wear-resistant green body formula slurry in step (1) is respectively added with 1% cobalt blue colorant, 2% wrapped red colorant, 3% orange colorant and 1% black colorant and then spray-dried to obtain;
[0057] The spray drying tower adopts a centrifugal spray drying system. The drying chamber diameter of the centrifugal drying system is 7000 mm, the drying output is 8 t / h, the rotation speed of the centrifugal atomizer is 150 r / s, and the particle gradation of the color powder is obtained: the particles under the 30 mesh sieve account for 100%, the particles between 40 mesh and 60 mesh account for 23%, the particles between 60 mesh and 80 mesh account for 42%, the particles between 80 mesh and 100 mesh account for 17%, and the particles below 100 mesh account for 1%. The specific gravity of the color powder is 1.1 g / cm 3 , the angle of repose is 30°;
[0058] ⑶ Modification of color powder, adding a surface modifier to the stale qualified color powder in step ⑵, and modifying the performance of the color powder by a dry mixing process to obtain a modified color powder;
[0059] The modified color powder is composed of the following components by weight percentage: color powder: 98wt%, surface modifier: 2wt%; the surface modifier is composed of calcium stearate and trimethoxysilane in a ratio of 1:1 by weight percentage;
[0060] (4) Whole-body fabric: the prepared modified color powders of different colors are formed into a three-dimensional decorative blank layer according to a preset pattern through a CNC fabric system;
[0061] The digital control material distribution system is an automatic operation technology directly controlled by digital information, and its structure includes four parts: central control device, material distribution device, transfer storage mechanism and transportation mechanism;
[0062] The central control device described in this embodiment is used for presetting, adjusting and outputting the CNC pattern and controlling the operation of the CNC material distribution system;
[0063] The material distribution device described in this embodiment arranges the blank layer according to the pattern texture preset by the above-mentioned central control device, and a total of three groups are set, and the aperture of the material distribution nozzle is 2mm;
[0064] The transfer storage mechanism described in this embodiment is provided with four groups in total, which are used to store four different color powders;
[0065] The transport mechanism described in this embodiment is used to connect the transfer storage mechanism and the material distribution device to ensure that the color powder can be accurately and quickly transported to the material distribution device for blank layer arrangement;
[0066] The three-dimensional decorative blank layer is formed by a CNC cloth system using CNC technology according to a preset pattern. The cloth texture forms a consistent pattern texture from the bottom to the top of the blank layer. The thickness of the cloth layer is 40 mm.
[0067] (5) Pressing and forming, pressing the blank layer into a wear-resistant blank;
[0068] The pressing pressure of the pressing molding is 45MPa / cm 2 , brick thickness 20mm;
[0069] (6) Printing the alignment code, and printing the code on the wear-resistant blank of step (5) according to the corresponding pattern number;
[0070] ⑺Dry the formed green body and spray water on the surface of the dried green body to moisten the surface;
[0071] The drying time is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0072] ⑻ Based on the formula of the polycrystalline wear-resistant green body in step ⑴, pigments and raw materials such as ceramic colorants and kaolin are introduced, and color slurry is obtained through calcination, grinding, spray drying and other processes;
[0073] The color pastes described in this embodiment are provided in eight kinds, which are:
[0074] The base slurry includes 99%+1% cobalt blue colorant, 97%+3% vanadium zirconium blue colorant, 98%+2% brown colorant, 998%+2% red colorant, 97%+3% orange colorant, 97%+3% yellow colorant, 99%+1% black colorant, and 98%+2% green colorant. After being prepared by weight percentage, the wet ball milling process is used to grind the color slurry. The specific gravity of the color slurry is 1.75g / cm 3 , 40° viscosity is 66mpa.s, D50 particle size is 12μm;
[0075] The base slurry described in this embodiment is composed of the following components by weight percentage: 89% of light-burned wear-resistant material, 9.72% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0076] The formula composition of the lightly fired wear-resistant material described in this embodiment is consistent with the formula of the polycrystalline wear-resistant blank in step (1), except that a lightly fired process is required; in the lightly fired process, the formula is prepared according to the weight percentage, and then ball-milled into a slurry according to a wet process; the slurry has a moisture content of 36%, a viscosity of 60 mpa.s at 40°, and a D50 particle size of 4 μm; the ball-milled slurry is spray-dried to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain the lightly fired wear-resistant material;
[0077] (9) Using the color slurry of step (8), according to the printing code of step (9), the wetted blank is sprayed with a digital spraying process in accordance with the same preset pattern as the blank to form a decorative wear-resistant layer;
[0078] The decorative wear-resistant layer is formed by using a CNC spraying process to perform decorative printing using a variety of different color slurries according to a preset pattern texture. The digital spraying pattern is the same as the pattern texture preset by the blank CNC cloth. The pattern is narrowed by 0.2mm, and the thickness of the decorative wear-resistant layer is 0.8mm.
[0079] The digital spraying process described in step (9) of this embodiment is a process of directly controlling the printing by using digital information, and the printing amount per square meter is 1400g;
[0080] ⑽ Applying slurry to the bottom of the green body in step ⑼;
[0081] ⑾ Send the green body coated with the base slurry into a roller kiln for high-temperature firing;
[0082] The high temperature firing adopts a kiln with a length of 380m, an inner width of 2.2m, a firing temperature of 1220°C, and a firing time of 75 minutes. After firing, the water absorption rate of the product is 0.06%, and the Ra value of the product out of the kiln is 1.72μm;
[0083] ⑿ Processing the fired products to obtain wear-resistant granite ceramic tiles with three-dimensional decorative effects;
[0084] The processing is specifically to polish the product obtained in step ⑾ first and then grind the edges, and the polishing is polishing of the decorative wear-resistant surface; polishing process parameters: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive block combination: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, and the Ra value of the product after polishing is 0.052μm.
[0085] Comparative Example 1:
[0086] Wear-resistant granite ceramic tiles with three-dimensional decorative effects, the body formula is composed of the following components by weight percentage (common body formula): 20% of 35# stone powder, 28% of ultra-white washed mud, 24% of potassium sodium stone powder, 10% of water-abrasive, 3% of superplastic soil, 5% of talc particles, 8.25% of common mud paste, 0.45% of body reinforcing agent, and 1.3% of degumming agent;
[0087] The difference between Comparative Example 1 and Example 1 is that the polycrystalline wear-resistant green body formula of Example 1 is replaced by a common green body formula. The preparation method of Comparative Example 1 is the same as that of Example 1.
[0088] Specifically, the methods of Example 1 and Comparative Example 1 were used to prepare granite ceramic tiles, and the obtained ceramic tiles and polished natural granite were tested for wear depth, flexural strength, water absorption, and Mohs hardness of unglazed tiles according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 1 below:
[0089] Table 1 Performance comparison of Example 1, Comparative Example 1 and natural granite (polished surface)
[0090]
[0091] The test results of Example 1, Comparative Example 1 and polished natural granite show that when the polycrystalline wear-resistant body formula of the present invention is replaced with a common body formula, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic plate will be significantly reduced. Figure 1 and Figure 2 The physical phase detection results show that the use of a polycrystalline wear-resistant green body formula generates more crystal phases than an ordinary green body formula, including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite and other high-hardness wear-resistant crystals. Not only are there many types of crystal phases, but also the content is high. Therefore, the wear resistance of the granite ceramic prepared in Example 1 is significantly higher than that of Comparative Example 1 and natural granite.
[0092] Comparative Example 2:
[0093] A method for preparing wear-resistant granite ceramic tiles with three-dimensional decorative effects comprises the following steps:
[0094] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: the raw materials in the green body formula are proportioned and ball-milled to obtain polycrystalline wear-resistant green body formula slurry, which is then sent to the transfer slurry pool for storage and aging after iron removal;
[0095] ⑵ Preparation of powders of different colors: according to the requirements of texture pattern design, a certain proportion of different color pigments are added to the polycrystalline wear-resistant blank formula slurry in step ⑴, stirred evenly and sent to a spray drying tower for powdering to obtain color powder and store it for aging for later use;
[0096] The color powder is provided in four types, specifically:
[0097] The polycrystalline wear-resistant green body formula slurry in step (1) is respectively added with 1% cobalt blue colorant, 2% wrapped red colorant, 3% orange colorant and 1% black colorant and then spray-dried to obtain;
[0098] The spray drying tower adopts a centrifugal spray drying system. The drying chamber diameter of the centrifugal drying system is 7000 mm, the drying output is 8 t / h, the rotation speed of the centrifugal atomizer is 150 r / s, and the particle gradation of the obtained color powder is: particles under 30 mesh account for 100%, particles between 40 mesh and 60 mesh account for 23%, particles between 60 mesh and 80 mesh account for 42%, particles between 80 mesh and 100 mesh account for 17%, particles below 100 mesh account for 1%, and the specific gravity of the color powder is 1.1 g / cm 3 , the angle of repose is 30°;
[0099] ⑶ Modification of color powder, adding a surface modifier to the stale qualified color powder in step ⑵, and modifying the performance of the color powder by a dry mixing process to obtain a modified color powder;
[0100] The modified color powder is composed of the following components by weight percentage: color powder: 98wt%, surface modifier: 2wt%;
[0101] The surface modifier is composed of calcium stearate and trimethoxysilane in a ratio of 1:1 by weight.
[0102] (4) Whole-body fabric: the prepared modified color powders of different colors are formed into a three-dimensional decorative blank layer according to a preset pattern through a CNC fabric system;
[0103] The digital control material distribution system is an automatic operation technology that is directly controlled by digital information. Its structure includes four parts: a central control device, a material distribution device, a transfer storage mechanism, and a transportation mechanism.
[0104] The central control device is used for presetting, adjusting and outputting the CNC pattern and controlling the operation of the CNC material distribution system;
[0105] The material distribution device arranges the blank layer according to the pattern texture preset by the above-mentioned central control device, and a total of 3 groups are set, and the aperture of the material distribution nozzle is 2mm;
[0106] The transfer storage mechanism is provided with 4 groups in total, which are used to store powders of four different colors;
[0107] The transport mechanism is used to connect the transfer storage mechanism and the material distribution device to ensure that the color powder can be accurately and quickly transported to the material distribution device for blank layer arrangement;
[0108] The three-dimensional decorative blank layer is formed by a CNC cloth system using CNC technology according to a preset pattern. The cloth texture forms a consistent pattern texture from the bottom to the top of the blank layer. The thickness of the cloth layer is 40 mm.
[0109] (5) Pressing and forming, pressing the blank layer into a wear-resistant blank;
[0110] The pressing pressure of the pressing molding is 45MPa / cm 2 , brick thickness 20mm;
[0111] (6) Printing the alignment code, and printing the code on the wear-resistant blank of step (5) according to the corresponding pattern number;
[0112] ⑺Dry the formed green body and spray water on the surface of the dried green body to moisten the surface;
[0113] The drying time is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0114] ⑻ Based on the formula of the polycrystalline wear-resistant green body in step ⑴, pigments and raw materials such as ceramic colorants and kaolin are introduced, and color slurry is obtained through calcination, grinding, spray drying and other processes;
[0115] The color slurries described in this embodiment are set to eight kinds, namely: basic slurry 99% + 1% cobalt blue colorant, basic slurry 97% + 3% vanadium zirconium blue colorant, basic slurry 98% + 2% brown colorant, basic slurry 998% + 2% wrapped red colorant, basic slurry 97% + 3% orange colorant, basic slurry 97% + 3% wrapped yellow colorant, basic slurry 99% + 1% black colorant, basic slurry 98% + 2% green colorant. After being prepared by weight percentage, they are ground into color slurries using a wet ball milling process. The specific gravity of the color slurry is 1.75g / cm 3 , 40° viscosity is 66mpa.s, D50 particle size is 12μm;
[0116] The basic slurry is composed of the following components by weight percentage: ball clay 9.72%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, CMC 0.32%, trimer 0.56%, defoamer 0.4%, after the formula is prepared by weight percentage, it is ball-milled into the basic slurry according to the wet process, the moisture content is controlled to 36%, the viscosity at 40° is 60mpa.s, and the D50 particle size is 4μm;
[0117] (9) Using the color slurry of step (8), according to the printing code of step (9), the wetted blank is sprayed with a digital spraying process in accordance with the same preset pattern as the blank to form a decorative wear-resistant layer;
[0118] The decorative wear-resistant layer is formed by using a CNC spraying process to perform decorative printing using a variety of different color slurries according to a preset pattern texture. The digital spraying pattern is the same as the pattern texture preset by the blank CNC cloth. The pattern is narrowed by 0.2mm, and the thickness of the decorative wear-resistant layer is 0.8mm.
[0119] The digital spraying process is a process that uses digital information to directly control the printing process, and the printing volume per square meter is 1400g;
[0120] ⑽ Applying slurry to the bottom of the green body in step ⑼;
[0121] ⑾ Send the green body coated with the base slurry into a roller kiln for high-temperature firing;
[0122] The high temperature firing adopts a kiln with a length of 380m and an inner width of 2.2m, a firing temperature of 1220°C, a firing time of 75 minutes, a water absorption rate of 0.06% after firing, and a Ra value of 1.72μm for the product out of the kiln;
[0123] ⑿ Processing the fired products to obtain wear-resistant granite ceramic tiles with three-dimensional decorative effects;
[0124] The processing is specifically to polish the product obtained in step ⑾ first, and then grind the edge, and the polishing is the polishing of the decorative wear-resistant surface. Polishing process parameters: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive block matching: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, Ra value of the product after polishing is 0.052μm;
[0125] The difference between Comparative Example 2 and Example 1 is that the decorative wear-resistant layer formula material is not subjected to light firing processing and is directly prepared and used according to the blank formula.
[0126] Specifically, granite ceramic tiles were prepared by the methods of Example 1 and Comparative Example 2, and the obtained ceramic tiles were tested for wear quality of 12,000 revolutions or flexural strength, water absorption, and Mohs hardness performance according to the national standard GB / T4100-2015 for ceramic tiles, and the results are shown in Table 2 below:
[0127] Table 2_Performance comparison between Example 1 and Comparative Example 2
[0128]
[0129] The test results of Example 1 and Comparative Example 2 show that when the decorative wear-resistant layer formula material of the present invention is not subjected to light firing, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic tile will decrease. Figure 1 and Figure 3 The phase detection results show that Figure 1 The types and contents of crystal phases are higher than Figure 3 This is because during the light firing process, various materials in the formula undergo a solid-phase reaction, generating a portion of wear-resistant crystal phase in advance. At the same time, after the calcination process, the reaction activity of the formula raw materials is improved, which promotes the formation of crystal phase during the secondary firing, so the wear resistance of the product can be better improved.
[0130] Embodiment 2:
[0131] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: the raw materials in the green body formula are proportioned and ball-milled to obtain polycrystalline wear-resistant green body formula slurry, which is then sent to the transfer slurry pool for storage and aging after iron removal;
[0132] The polycrystalline wear-resistant blank formula is composed of the following components by weight percentage: 9.55% ball clay, 10% high white kaolin, 12% mixed mud, 4% burned talc, 4% bentonite, 19% potassium sodium stone powder, 10% finely ground lithium tailings, 5% calcined bauxite, 20% fine corundum powder, 3% ultrafine zirconium silicate, 2% high-purity anatase titanium dioxide powder, 0.35% blank reinforcing agent, and 1.1% debonding agent.
[0133] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.94%, a Fe2O3 content of 0.06%, and a particle size D50 of 1.86 μm.
[0134] The chemical composition of the finely ground lithium tailings is as follows by weight percentage: Al2O3 17.83wt%, SiO2 69.11wt%, K2O 3.50wt%, Fe2O3 0.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li2O 0.41wt%, trace elements 0.18wt%, ignition loss 3.39wt%. The particle size D50 is 5.4μm, and the trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel;
[0135] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0136] The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of 98.6%, a powder whiteness value of 97.2%, a volatile matter of 0.3% at 105°, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;
[0137] ⑵ Preparation of powders of different colors: according to the requirements of texture pattern design, a certain proportion of different color pigments are added to the polycrystalline wear-resistant blank formula slurry in step ⑴, stirred evenly and sent to a spray drying tower for powdering to obtain color powder and store it for aging for later use;
[0138] The color powder is provided in four types, specifically, the polycrystalline wear-resistant blank formula slurry in step (1) is respectively added with 1% cobalt blue colorant, 2% wrapped red colorant, 3% orange colorant, and 1% black colorant, and then spray-dried;
[0139] The spray drying tower adopts a centrifugal spray drying system. The drying chamber diameter of the centrifugal drying system is 7000 mm, the drying output is 8 t / h, the rotation speed of the centrifugal atomizer is 150 r / s, and the particle gradation of the color powder is obtained: the particles under the 30 mesh sieve account for 100%, the particles between 40 mesh and 60 mesh account for 23%, the particles between 60 mesh and 80 mesh account for 42%, the particles between 80 mesh and 100 mesh account for 17%, and the particles below 100 mesh account for 1%. The specific gravity of the color powder is 1.1 g / cm 3 , the angle of repose is 30°.
[0140] ⑶ Modification of color powder, adding a surface modifier to the stale qualified color powder in step ⑵, and modifying the performance of the color powder by a dry mixing process to obtain a modified color powder;
[0141] The modified color powder is composed of the following components by weight percentage: color powder: 98wt%, surface modifier: 2wt%;
[0142] The surface modifier is composed of calcium stearate and trimethoxysilane in a ratio of 1:1 by weight.
[0143] (4) Whole-body fabric: the prepared modified color powders of different colors are formed into a three-dimensional decorative blank layer according to a preset pattern through a CNC fabric system;
[0144] The numerical control material distribution system is an automatic operation technology directly controlled by digital information, and its structure includes four parts: a central control device, a material distribution device, a transfer storage mechanism and a transportation mechanism.
[0145] The central control device is used for presetting, adjusting and outputting the CNC pattern and controlling the operation of the CNC material distribution system;
[0146] The material distribution device arranges the blank layer according to the pattern texture preset by the central control device, and a total of three groups are set, and the aperture of the material distribution nozzle is 2mm;
[0147] The transfer storage mechanism is provided with four groups in total, which are used to store four different color powders;
[0148] The transport mechanism is used to connect the transfer storage mechanism and the material distribution device to ensure that the color powder can be accurately and quickly transported to the material distribution device for blank layer arrangement;
[0149] The three-dimensional decorative blank layer is formed by a CNC cloth system using CNC technology according to a preset pattern. The cloth texture forms a consistent pattern texture from the bottom to the top of the blank layer. The thickness of the cloth layer is 40 mm.
[0150] (5) Pressing and forming, pressing the blank layer into a wear-resistant blank;
[0151] The pressing pressure of the pressing molding is 45MPa / cm 2 , brick thickness 20mm;
[0152] (6) Printing the alignment code, and printing the code on the wear-resistant blank of step (5) according to the corresponding pattern number;
[0153] ⑺Dry the formed green body and spray water on the surface of the dried green body to moisten the surface;
[0154] The drying time is 110 minutes; the residual moisture of the green body after drying is 0.42%.
[0155] ⑻ Based on the formula of the polycrystalline wear-resistant green body in step ⑴, pigments and raw materials such as ceramic colorants and kaolin are introduced, and color slurry is obtained through calcination, grinding, spray drying and other processes;
[0156] The color slurry is provided with eight kinds, specifically: basic slurry 99% + 1% cobalt blue colorant, basic slurry 97% + 3% vanadium zirconium blue colorant, basic slurry 98% + 2% brown colorant, basic slurry 998% + 2% wrapped red colorant, basic slurry 97% + 3% orange colorant, basic slurry 97% + 3% wrapped yellow colorant, basic slurry 99% + 1% black colorant, basic slurry 98% + 2% green colorant. After being prepared by weight percentage, the color slurry is ground into color slurry by wet ball milling process. The specific gravity of the color slurry is 1.75g / cm 3 , 40° viscosity is 66mpa.s, D50 particle size is 12μm;
[0157] The base slurry is composed of the following components by weight percentage: 89% of light-burned wear-resistant material, 9.72% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0158] The formula composition of the lightly fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank in step (1), except that it needs to be lightly fired; the lightly fired process is to prepare the formula according to the weight percentage and then ball-mill it into slurry according to the wet process; the slurry has a moisture content of 36%, a viscosity of 60mpa.s at 40°, and a D50 particle size of 4μm. The ball-milled slurry is spray-dried to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain the lightly fired wear-resistant material;
[0159] (9) Using the color slurry of step (8), according to the printing code of step (9), the wetted blank is sprayed with a digital spraying process in accordance with the same preset pattern as the blank to form a decorative wear-resistant layer;
[0160] The decorative wear-resistant layer is formed by using a CNC spraying process to perform decorative printing using a variety of different color slurries according to a preset pattern texture. The digital spraying pattern is the same as the pattern texture preset by the blank CNC cloth. The pattern is narrowed by 0.2mm, and the thickness of the decorative wear-resistant layer is 0.8mm.
[0161] The digital spraying process is a process that uses digital information to directly control the printing process, and the printing volume per square meter is 1400g;
[0162] ⑽ Applying slurry to the bottom of the green body in step ⑼;
[0163] ⑾ Send the green body coated with the base slurry into a roller kiln for high-temperature firing;
[0164] The high temperature firing adopts a kiln with a length of 380m and an inner width of 2.2m, a firing temperature of 1220°C, a firing time of 75 minutes, a water absorption rate of 0.06% after firing, and a Ra value of 1.72μm for the product out of the kiln;
[0165] ⑿ Processing the fired products to obtain wear-resistant granite ceramic tiles with three-dimensional decorative effects;
[0166] The processing specifically includes: only grinding the edge of the product obtained in step ⑾ without polishing.
[0167] Granite ceramic tiles were prepared by the method of Example 2, and the obtained ceramic tiles and natural granite were tested for unglazed tile wear depth, flexural strength, water absorption, and Mohs hardness according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 3 below:
[0168] Table 3 Example 2 and natural granite
[0169]
[0170] It can be seen from the test results of Example 2 and natural granite that the granite ceramic tile prepared by the method of Example 2 has better wear resistance, Mohs hardness and flexural strength than natural granite. This is because the granite ceramic tile prepared by the method of Example 2 produces more high-hardness wear-resistant crystals, including mullite, corundum, zircon, quartz, rutile, anorthite, etc., where the Mohs hardness of mullite and anorthite reaches 6, rutile is 6-6.5, zircon is 7.5-8, and corundum is 9. These high-hardness wear-resistant crystals are not only of many types, but also of high content, thereby improving the wear resistance of the product.
[0171] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.
Claims
1. A wear-resistant granite ceramic tile with three-dimensional decorative effect, characterized in that: The polycrystalline wear-resistant blank formula is composed of the following components by weight percentage: 8% to 15% of ball clay, 8% to 15% of high white kaolin, 10% to 15% of mixed mud, 0% to 5% of burned talc, 3% to 6% of bentonite, 15% to 25% of potassium sodium stone powder, 8% to 15% of finely ground lithium tailings, 4% to 8% of calcined bauxite, 15% to 25% of fine corundum powder, 0% to 5% of ultrafine zirconium silicate, 0% to 5% of high-purity anatase titanium dioxide powder, 0% to 1% of blank reinforcing agent, and 1% to 3% of debonding agent; the fine corundum powder is α-Al2O3 with an Al2O3 content of 99.9 to 100%, an Fe2O3 content of 0 to 0.1%, and the particle size D50 is less than 3μm.
2. The wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 1, characterized in that: The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O 30-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3~1wt%, trace elements ≥0.1wt%, ignition loss 0~5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm; the trace elements include rubidium, gallium, strontium, cadmium, and nickel; the ZrO2 content of the ultrafine zirconium silicate is greater than 64%, and the particle size D50 is less than 1μm; the high-purity anatase titanium dioxide powder is anatase titanium dioxide with a TiO2 content greater than 98%, a powder whiteness value greater than 96%, 105° volatile matter ≤0.5%, a 325 mesh sieve residue less than 0.1%, and a particle size D50 less than 1μm.
3. A method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 1, characterized in that: The following steps are involved: ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain polycrystalline wear-resistant green body formula slurry, and after iron removal, send it to the transfer slurry pool for storage and aging for standby use; (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, add different color pigments of set proportions to the polycrystalline wear-resistant blank formula slurry in step (1), stir evenly and send to the spray drying tower for powdering to obtain color powder and store it for aging for later use; ⑶ Modification of color powder: adding a surface modifier to the aged qualified color powder in step ⑵, and modifying the performance of the color powder by a dry mixing process to obtain a modified color powder; (4) Whole-body fabric: The prepared modified color powders of different colors are formed into a three-dimensional decorative blank layer according to a preset pattern through a CNC fabric system; ⑸ Pressing and molding: Pressing the blank layer into a wear-resistant blank; (6) Printing alignment code: Printing code on the wear-resistant blank of step (5) according to the corresponding pattern number; ⑺Dry the formed green body and spray water on the surface of the dried green body to moisten the surface; ⑻ Based on the multi-crystalline wear-resistant body formula in step ⑴, ceramic colorant, kaolin color slurry and raw materials are introduced, and color slurry is obtained through calcination, grinding and spray drying; (9) Using the color slurry of step (8), according to the printing code of step (9), the wetted blank is sprayed with a digital spraying process in accordance with the same preset pattern as the blank to form a decorative wear-resistant layer; ⑽ The bottom of the green body in step ⑼ is coated with base slurry; ⑾ Send the green body coated with the base slurry into a roller kiln for high-temperature firing; ⑿ Processing the fired products to obtain wear-resistant granite ceramic tiles with three-dimensional decorative effects.
4. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: The different color pigments described in step (2) include ceramic pigments of different colors such as blue, red, yellow, black, and green; the color powder is provided with 3 to 6 different colors according to the design requirements; the spray drying tower in step (2) adopts a centrifugal spray drying system; the drying chamber diameter of the centrifugal drying system is greater than 5000 mm, the drying output is 5 to 10 t / h, the speed of the centrifugal atomizer is controlled to be 50 to 350 r / s, and the particle gradation of the color powder is obtained: the particles under the 30 mesh sieve account for 100%, the particles between 40 mesh and 60 mesh account for 20% to 25%, the particles between 60 mesh and 80 mesh account for 40% to 45%, the particles between 80 mesh and 100 mesh account for 15% to 20%, the particles below 100 mesh account for <3%, and the specific gravity of the color powder is 1.0 to 1.2 g / cm 3 , the angle of repose is 30°~32°.
5. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: Step (3) The modified color powder is composed of the following components by weight percentage: color powder: 97-99wt%, surface modifier: 1-3wt%; the surface modifier is one or a combination of the following: calcium stearate, aluminum stearate, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid-polyoxyethylene, aminopropyl triethoxysilane, trimethoxysilane, dimethoxysilane, polyphosphate, alkylbenzene sulfonate; Step (5) of the compression molding process, the compression pressure is > 40 MPa / cm 2 , brick thickness 9mm~40mm; The drying time in step (7) is 50 to 120 minutes; the residual moisture of the green body after drying is ≤0.5%.
6. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: Step (4) The CNC material distribution system is an automatic operation technology directly controlled by digital information, which can simultaneously realize the distribution of 4 to 10 different color powders. Its structure includes four parts: a central control device, a material distribution device, a transfer storage mechanism and a transportation mechanism; the central control device is used for presetting, adjusting and outputting CNC patterns, and controlling the operation of the CNC material distribution system; the material distribution device arranges the blank layer according to the pattern texture preset in the central control device, and several groups can be set according to the thickness requirements of the blank layer, and the aperture of the material distribution nozzle is 1 to 5 mm; the transfer storage mechanism is used to store powders of different colors, and 4 to 10 groups are set according to the distribution needs; the transportation mechanism is used to connect the transfer storage mechanism and the material distribution device to ensure that the color powder can be accurately and quickly transported to the material distribution device for blank layer arrangement; the three-dimensional decorative blank layer is formed by the CNC material distribution system using CNC technology according to the preset pattern, and the cloth texture is a consistent pattern texture formed from the bottom to the top of the blank layer, and the thickness of the material layer is 18 mm to 80 mm.
7. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: The color slurry described in step ⑻ is composed of the following components by weight percentage: 95-99% of base slurry and 1-5% of ceramic colorant; after being prepared by weight percentage, the color slurry is obtained by stirring evenly, and the specific gravity of the color slurry is 1.75±0.5g / cm 3 , 40° viscosity is 60-150mpa.s, D50 particle size is 10μm-15μm; the ceramic pigment is composed of one or more pigments of blue, red, yellow, black and green; the base slurry is composed of the following components by weight percentage: lightly calcined wear-resistant material 78-90%, kaolin 8-20%, CMC 0.2-1%, trimer 0.5-1%, defoamer 0.2-1%; the formula composition of the light-fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank, the difference is that light-fired processing is required; the light-fired processing is: after the formula is prepared according to the weight percentage, it is ball-milled into mud according to the wet process; the mud has a moisture content of 35-40%, a viscosity of 40° is 40-80mpa.s, and a D50 particle size is 3-6μm; the ball-milled mud is spray-dried to obtain a powder, the obtained powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1050-1150°C to obtain the light-fired wear-resistant material.
8. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: The decorative wear-resistant layer described in step (9) is formed by decorative printing using a plurality of different color slurries according to a preset pattern texture using a CNC spraying process. The digital spraying pattern is the same as the pattern texture preset by the CNC cloth of the blank. The pattern is narrowed by 0.2mm to 0.4mm, and the thickness of the decorative wear-resistant layer is 0mm to 1mm. The digital spraying process uses digital information to directly control the printing, and can simultaneously realize the printing of 4 to 10 different color slurries, and the printing amount per square is controlled to be 0 to 1800g.
9. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: The high temperature firing described in step ⑾ adopts a kiln length of more than 300m, an inner width greater than 2m, a firing temperature of 1180-1250°C, a firing time of 60-120 minutes, a water absorption rate of the product after firing of ≤0.5%, and a Ra value of the product out of the kiln, which refers to the arithmetic mean deviation of the profile, that is, the surface roughness is between 1.5 and 3μm.
10. The method for preparing the wear-resistant granite ceramic tile with three-dimensional decorative effect according to claim 3, characterized in that: The processing described in step ⑿ includes two situations: ⑴ Grind the edges of the product after firing in step ⑾ directly; (2) The product obtained in step (10) is first polished and then edged; Among them, the polishing is the polishing of the wear-resistant surface; the polishing process parameters are: the polishing machine pressure is below 0.6Mpa, the polishing speed is 15-30m / min, the polishing abrasive blocks are matched as follows: 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, the polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.
Citation Information
Patent Citations
Process for producing large-grain granite imitated ceramic tiles with stone surface effect
CN106747379A
Lithium mine tailing lightweight ceramic sheet material manufacturing method
CN108911778A
Thin ceramic rock plate and preparation method thereof
CN111470856A
Ceramic rock plate with multicolor light-transmitting three-dimensional effect and manufacturing method thereof
CN113896569A
Ultrathin ceramic rock plate and preparation method thereof
CN114436625A